2017
DOI: 10.1186/s12875-017-0635-z
|View full text |Cite
|
Sign up to set email alerts
|

Health care resource use by patients before and after a diagnosis of chronic fatigue syndrome (CFS/ME): a clinical practice research datalink study

Abstract: BackgroundOur aim was to investigate patterns of health care resource use by patients before and after a diagnosis of CFS/ME, as recorded by Clinical Practice Research Datalink (CPRD) GP practices in the UK.MethodsWe used a case–control study design in which patients who had a first recorded diagnosis of CFS/ME during the period 01/01/2001 to 31/12/2013 were matched 1:1 with controls by age, sex, and GP practice. We compared rates of GP consultations, diagnostic tests, prescriptions, referrals, and symptoms be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Children with CFS/ME have an increase in medical consultations, tests, and prescriptions, up to five years before receiving a diagnosis. 8 Most children attending a specialist service attended 40% of school or less. 9 About one-third of them suffer from comorbid anxiety and/or depression.…”
Section: Introductionmentioning
confidence: 99%
“…Children with CFS/ME have an increase in medical consultations, tests, and prescriptions, up to five years before receiving a diagnosis. 8 Most children attending a specialist service attended 40% of school or less. 9 About one-third of them suffer from comorbid anxiety and/or depression.…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis of electronic primary care data in the UK showed that children with CFS/ME had substantially higher healthcare needs than matched population controls for at least 10 years before their diagnosis. 39 This suggests that parents have underestimated the duration of their child’s fatigue, or that paediatric CFS/ME begins in a mild form which develops into more severe CFS/ME. This is plausible if the milder form of CFS/ME does not lead to notable absences from school or college.…”
Section: Discussionmentioning
confidence: 99%
“…CFS/ME has a significant impact on the lives of young people; it is associated with significant physical disability, school absences, social and emotional difficulties and some children have periods of being bedbound (Bould, Lewis, Emond, & Crawley, 2011; Carter, Edwards, Kronenberger, Michalczyk, & Marshall, 1995; Dowsett & Colby, 1997; Garralda & Rangel, 2004; Patel, Smith, Chalder, & Wessely, 2003). CFS/ME also affects the whole family (Velleman, Collin, Beasant, & Crawley, 2016) and is costly for the Health Service (NHS) (Collin, Bakken, Nazareth, Crawley, & White, 2017). Despite this, it is an overlooked and stigmatised condition (Anderson, Jason, Hlavaty, Porter, & Cudia, 2012).…”
Section: Introductionmentioning
confidence: 99%